Juridical Overview Of Ulayat Land Dispute Resolution And Its Existence - Dedy Hernawan (Jurnal Info Sains : Informatika dan Sains, 2023)
This study give clear picture about complexity conflict land ulayat in Indonesia and its importance confession as well as protection to right customary law as solution for solution conflict in public. This study use approach qualitative juridical with dig depth presenting issue analysis deep . Emphasis on recognition and protection right customary law as part from system law agrarian national show that awareness importance enter values local and wisdom local in regulations law national. This is important No only guard justice for public custom but create certainty necessary laws for all holder interest. Confession to right customary law No only formal , but also necessary accompanied with effective implementation in the field . This matter covers improvement awareness and understanding public as well as enforcement consistent law, and justice from party authorized . Customary rights as alternative solution conflict land that has not resolved, therefore with approach in a way holistic and inclusive in solution dispute land customary, can contribute in create environment conducive and stable social, economic, and political, as well support realization orderly administration land in a way overall in Indonesia.